2010
DOI: 10.3844/ajessp.2010.316.323
|View full text |Cite
|
Sign up to set email alerts
|

Representative Particle Size of Sediment in Storm Sewer Inlets

Abstract: Problem statement: The aim of this study was examine the representative particle size of noncohesive sediment samples collected from different storm sewer inlets in residential catchments within Kuwait. Approach: A number of 25 sediment samples were collected from storm sewer inlets located in five residential areas in Kuwait: Bayan, Al-Nuzha, Al-Feiha, Al-Andalos and Al-Rumaithya. All the impervious areas for the selected sites are hydraulically connected to the drainage system, including the roofs for houses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The 10 locations are Bandar Kangar, Butterworth, Ipoh, Shah Alam, Seremban, Kuantan, Kuala Terengganu, Kota Bahru, Kuching (residential) and Kuching (commercial). This has some similarity to the sediment samples from 5 residential areas in Kuwait where the samples skewed to the right [9]. This showed that most of the samples were not of normal distribution, thus using the median diameter, 50 d might not be a good representative of the sediment samples size.…”
Section: Results and Analysissupporting
confidence: 52%
See 2 more Smart Citations
“…The 10 locations are Bandar Kangar, Butterworth, Ipoh, Shah Alam, Seremban, Kuantan, Kuala Terengganu, Kota Bahru, Kuching (residential) and Kuching (commercial). This has some similarity to the sediment samples from 5 residential areas in Kuwait where the samples skewed to the right [9]. This showed that most of the samples were not of normal distribution, thus using the median diameter, 50 d might not be a good representative of the sediment samples size.…”
Section: Results and Analysissupporting
confidence: 52%
“…Mean, being the average of the particle size varies depending on the nature of the sediment data; while median may become sensitive to the shape of the data set distribution and often does not depict the typical outcome. Mode, on the other hand is less bias due to the nature of mode that always represent the highest percentage of particle by weight [9].…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantage of designing a sewer with a rectangular cross section is the flexibility of selecting a channel depth and changing the width to acquire larger flows, while in circular sections the sewer size is proportional to the pipe diameter. A common problem in sewer design is to avoid sediment deposition at the bottom of the conduit (Kleijwegt, 1992;Almedeij et al, 2010). This problem has adverse impact on the environment as the sediment can act as pollution store or generator that can be washed out by the first flush into receiving water (Artina et al, 2007;Almedeij et al, 2010;Mannina and Viviani, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A common problem in sewer design is to avoid sediment deposition at the bottom of the conduit (Kleijwegt, 1992;Almedeij et al, 2010). This problem has adverse impact on the environment as the sediment can act as pollution store or generator that can be washed out by the first flush into receiving water (Artina et al, 2007;Almedeij et al, 2010;Mannina and Viviani, 2010). The deposits under severe conditions may also cause early water surcharge resulting with a reduction in conduit hydraulic capacity (Ackers, 1991).…”
Section: Introductionmentioning
confidence: 99%